Analysis of threats spread of Ukraine financial security in a pandemic (Economics and region, 2020)
Theoretical principles of financial security and its place in the general system of the national economy were covered. It is noted that from the standpoint of the protective approach the key category of financial security is the threat, the source of which is the uncertainty caused by the properties of social phenomena and processes. The economic essence of threats was revealed and their impact on the financial security of business was characterized. The main destructive factors of the shadow economy and corruption on financial security were studied and the reasons for their spread in Ukraine were highlighted. Trends in the level of financial security in the context of comparing it with regulatory values were analyzed. It is proved that the global challenge to financial security of business and the state as a whole is the COVID-19 pandemic, which is a catalyst for real and potential threats with the maximum level of impact on the financial condition and financial results of business entities in modern conditions. Corruption and the shadow economy were considered according to different methodological approaches, as well as on the basis of correlation-regression analysis. The relationship between the impact of corruption and the shadow economy on the level of financial security of Ukraine has been determined. A high direct linear relationship between the levels of financial security of Ukraine and the shadow economy and corruption was detected. The impact of threats on the financial security of business in Ukraine in a pandemic was analyzed and assessed. It is proved that development of business and ensuring its target parameters of financial security in a crisis would minimize the negative impact of modern threats associated with quarantine restrictions. The priority directions of minimization of threats to financial security of business in the conditions of epidemic danger were defined. It is proved that adaptive management in the face of real threats can minimize financial risks for business and create a foundation for further business development in the post-crisis period, when the impact of the threat would be reduced.
Keywords: financial security; corruption; shadow economy; business security; challenge; threat; pandemic